Homogeneous Palladium Diselenide pn‐Junction Diodes for Reconfigurable Circuit Applications (Adv. Electron. Mater. 10/2022). (10th October 2022) - Lee, Minjong; Park, Chang Yong; Sim, Sangjun; Lee, Kimoon; Lee, Young Tack
Abstract : Reconfigurable Diode Circuit Applications Palladium diselenide (PdSe2 ) has recently emerged as a 2D material that has strong ambipolar property and air stability for use in future nano‐electronic devices. Ambipolar semiconductor could easily accumulate the electron or hole carriers at the channel material by gate field modulation. Kimoon Lee, Young Tack Lee, and co‐workers in article number 2101282 present the PdSe2 ‐based split‐gate field‐effect transistor which can be formed as a switchable diode (like a one way road) and single‐inversion AND (SAND) logic gate as well.